2004
DOI: 10.1212/01.wnl.0000128136.79044.d6
|View full text |Cite
|
Sign up to set email alerts
|

Randomized multicenter trial of natalizumab in acute MS relapses

Abstract: A single dose of IV natalizumab did not hasten clinical recovery after relapse, although a significant decrease in Gd-enhancing lesion volume was observed at 1 and 3 weeks after treatment. These MRI findings are consistent with prior studies of natalizumab and support its further investigation as an agent for the treatment of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(81 citation statements)
references
References 17 publications
2
75
0
4
Order By: Relevance
“…Twelve articles, relating to five randomized controlled trials (RCTs), met our inclusion criteria. [12][13][14][15][16][17][18][19][20][21][22][23] In addition, a sixth RCT (the GLANCE trial comparing the combination of natalizumab and glatiramer acetate to glatiramer acetate alone) had sufficient data presented for classification. 24 Each panel member read each article and classified the level of evidence for the clinical trials according to the system used by the American Academy of Neurology for therapeutic interventions (available as supplemental data on the Neurology ® Web site at www.…”
Section: Description Of the Analytic Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve articles, relating to five randomized controlled trials (RCTs), met our inclusion criteria. [12][13][14][15][16][17][18][19][20][21][22][23] In addition, a sixth RCT (the GLANCE trial comparing the combination of natalizumab and glatiramer acetate to glatiramer acetate alone) had sufficient data presented for classification. 24 Each panel member read each article and classified the level of evidence for the clinical trials according to the system used by the American Academy of Neurology for therapeutic interventions (available as supplemental data on the Neurology ® Web site at www.…”
Section: Description Of the Analytic Processmentioning
confidence: 99%
“…neurology.org). 16,18,26 Three additional RCTs studied both clinical and MRI outcomes. 17,19,[22][23][24] Two compared natalizumab to placebo 15,17,20,22 and the other studied the combination of natalizumab and IFN␤-1a (Avonex) 30 g per week IM compared to IFN␤-1a alone.…”
Section: Description Of the Analytic Processmentioning
confidence: 99%
“…Several alternatives, including plasmapheresis [48][49][50][51], cyclophosphamide [48,52,53], intravenous immunoglobulin G (IV-IG) [54][55][56][57][58], and natalizumab [59] have been studied with plasmapheresis as the only option supported by strong clinical evidence. The recent American Academy of Neurology guideline published in January 2011 [60] recommends considering using plasma exchange as a secondary treatment for severe flares in remitting-relapsing MS.…”
Section: Second Line Of Treatment For Ms Relapse Cases Unresponsive Tmentioning
confidence: 99%
“…Natalizumab acts via the blockade of the VLA-4 receptor, which plays a significant role in leukocyte migration into the brain parenchyma (Rudick and Sandrock, 2004). Clinical studies with Natalizumab have shown this drug to have high efficacy in terms of its ability to prevent disease relapses and progression (Chaudhuri and Behan, 2003;O'Connor et al, 2004). However, this efficacy comes at the cost of some significant safety issues.…”
Section: Current Clinical Strategies In Multiple Sclerosis To Modify mentioning
confidence: 99%